Cell specificity of magnetic cell seeding approach to hydrogel colonization. Issue 11 (14th July 2017) - Singh, Raminder; Wieser, Anna; Reakasame, Supachai; Detsch, Rainer; Dietel, Barbara; Alexiou, Christoph; Boccaccini, Aldo R.; Cicha, Iwona
Abstract: Tissue‐engineered scaffolds require an effective colonization with cells. Superparamagnetic iron oxide nanoparticles (SPIONs) can enhance cell adhesion to matrices by magnetic cell seeding. We investigated the possibility of improving cell attachment and growth on different alginate‐based hydrogels using fibroblasts and endothelial cells (ECs) loaded with SPIONs. Hydrogels containing pure alginate (Alg), alginate dialdehyde crosslinked with gelatin (ADA‐G) and Alg blended with G or silk fibroin (SF) were prepared. Endothelial cells and fibroblasts loaded with SPIONs were seeded and grown on hydrogels for up to 7 days, in the presence of magnetic field during the first 24 h. Cell morphology (fluorescent staining) and metabolic activity (WST‐8 assay) of magnetically‐seeded versus conventionally seeded cells were compared. Magnetic seeding of ECs improved their initial attachment and further growth on Alg/G hydrogel surfaces. However, we did not achieve an efficient and stable colonization of ADA‐G films with ECs even with magnetic cell seeding. Fibroblast showed good initial colonization and growth on ADA‐G and on Alg/SF. This effect was further significantly enhanced by magnetic cell seeding. On pure Alg, initial attachment and spreading of magnetically‐seeded cells was dramatically improved compared to conventionally‐seeded cells, but the effect was transient and diminished gradually with the cessation of magnetic force. Our results demonstrate that magnetic seeding improves the strength and uniformity of initial cell attachment to hydrogel surface in cell‐specific manner, which may play a decisive role for the outcome in tissue engineering applications. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2948–2956, 2017.